Implementasi Kebijakan Pelayanan Publik dalam Penerbitan Kartu Identitas Anak di Kabupaten Badung - I Gede Prana Prabangkara; Ketut Kasta Arya Wijaya; Luh Putu Suryani (Jurnal Preferensi Hukum, 2022)
Child Identity Card (KIA) is considered important considering that until now there is no identity card for children, even though the child already has a birth certificate and or of course has a student card. This has prompted the government to create programs related to Child Identity. The purposes of this study are to examine the regulation of the issuance of child identity cards in Badung Regency and the inhibiting factors of public service for children's identity cards in Badung Regency. The type of research used is empirical legal research with a case and statutory approach. Sources of data in this study are primary and secondary data. Data collection techniques were carried out by interviews and documentation techniques. After the legal materials are collected, they are processed and analyzed qualitatively. The findings reveal that the regulation on the issuance of Child Identity Cards in Badung Regency is carried out at the Population and Civil Registry Office (Dispendukcapil) of Badung Regency based on Law Number 25 of 2009 concerning Public Services. The inhibiting factors for the Child Identity Card (KIA) service in Badung Regency are the disposition and organizational structure as well as the facilities and infrastructure owned